Cytoprotective properties of the nerve growth factor and brain derived neurotrophic factor dipeptidic mimetics, GK-2 AND GSB-106, in the model of oxidative stress in paramecium caudatum - O. V. Karpukhina; A. N. Inozemtsev; K. Z. Gumargalieva; P. Yu. Povarnina; T. A. Gudasheva (Фармакокинетика и Фармакодинамика, 2018)
Resume. Actuality. Dimeric dipeptide mimics of the nerve growth factor ( NGF) and brain derived neurotrophic factor (BDNF), respectively GK-2 and GSB-106, were created in the V.V. Zakusov Institute of pharmacology. The similarity of GK-2 and GSB-106 to the corresponding full-sized neurotrophins by the mechanism of action and pharmacological properties, including pronounced neuroprotective activity in vitro and in vivo, has been established. The purpose of this study was to obtain additional data on the cytoprotective properties of GK-2 and GSB-106 using Paramecium caudatum. Methods. Oxidative stress in the Paramecium caudatum was induced by adding heavy metal salts (cadmium chloride, lead acetate, copper sulfate, zinc sulfate) to the medium at a final concentration of 10 |jM. GK-2 or GSB-106 in concentrations from 10-5 to 10-8 M was added into the medium with experimental cells 45 minutes before introducing the oxidative stress initiator. Results. Dipeptides GK-2 and GSB-106 in all studied concentrations protected cells from death. The maximum neuroprotective effect of the dipeptides showed in a concentration of 10-8 M, completely preventing the death of ciliates. Conclusion. GK-2 and GSB-106, at a concentration of 10-8M, completely protect against the death Paramecium caudatum under conditions of oxidative stress caused by heavy metal salts.